2018
DOI: 10.1002/jor.24153
|View full text |Cite
|
Sign up to set email alerts
|

Preclinical induced membrane model to evaluate synthetic implants for healing critical bone defects without autograft

Abstract: Critical bone defects pose a formidable orthopaedic problem in patients with bone loss. We developed a preclinical model based on the induced membrane technique using a synthetic graft to replace autograft for healing critical bone defects. Additionally, we used a novel osteoconductive scaffold coupled with a synthetic membrane to evaluate the potential for single‐stage bone regeneration. Three experimental conditions were investigated in critical femoral defects in rats. Group A underwent a two‐stage procedur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
40
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 25 publications
(41 citation statements)
references
References 53 publications
1
40
0
Order By: Relevance
“…The time point for pharmaceutical interventions as well as the concentrations of BMP-7 and bisphosphonate used were determinants in the success of the healing. Of note, insertion of a 3D printed polycaprolactone (PLC)/β-tricalcium phosphate (β-TCP) scaffold in a rat IM model has been shown to support bone formation (DeBaun et al, 2018). It was not the case when a natural coral scaffold (99% calcium carbonate and 1% organic material) was used to fill in the IM in a sheep model (Viateau et al, 2007).…”
Section: Mesenchymal Stem Cellsmentioning
confidence: 99%
See 1 more Smart Citation
“…The time point for pharmaceutical interventions as well as the concentrations of BMP-7 and bisphosphonate used were determinants in the success of the healing. Of note, insertion of a 3D printed polycaprolactone (PLC)/β-tricalcium phosphate (β-TCP) scaffold in a rat IM model has been shown to support bone formation (DeBaun et al, 2018). It was not the case when a natural coral scaffold (99% calcium carbonate and 1% organic material) was used to fill in the IM in a sheep model (Viateau et al, 2007).…”
Section: Mesenchymal Stem Cellsmentioning
confidence: 99%
“…The replacement of the IM by a PLC-based film did not improve bone regeneration in rat. (DeBaun et al, 2018).…”
Section: Mesenchymal Stem Cellsmentioning
confidence: 99%
“…Treatment of bone defects of a critical size remains a serious challenge in surgery and orthopedics. Segment defects are the result of various injuries, infections, resections of tumors of various localization, as well as congenital deformity of bone development (1,2,4). Conceivably, bone defects of a critical size do not heal spontaneously, despite the surgical stabilization (3,4).…”
Section: Introductionmentioning
confidence: 99%
“…Segment defects are the result of various injuries, infections, resections of tumors of various localization, as well as congenital deformity of bone development (1,2,4). Conceivably, bone defects of a critical size do not heal spontaneously, despite the surgical stabilization (3,4). The method of using autologous bone grafts in reconstructive surgery for congenital malformations and defects caused by some trauma or disease, as well as for cosmetic procedures in certain parts of the body, have their disadvantages, such as a limited bone scraping, non-identity of bone shape, discomfort and pain in the area of the donor site.…”
Section: Introductionmentioning
confidence: 99%
“…We used the filaments and subcutaneous implantation as a simple screening test before we test them in bone defects. In our other studies, we implanted 3D-printed TCP/PCL scaffolds of single formulation (20% TCP/80% PCL) into large bone defects in rabbit femoral heads [13,14] and rat femurs [46]. Both implantations showed that our scaffolds promoted bone ingrowth into the porous structure and retained structural integrity, suggesting excellent biocompatibility and osteointegration.…”
Section: Histological Examinationmentioning
confidence: 84%